Mycobacterium bovis-induced Aneurysm after Intravesical Bacillus Calmette-Guérin Therapy: A Case Study and Literature Review - Higashi, Yoshitsugu; Nakamura, Shigeki; Kidani, Kento; Matumoto, Kaoru; Kawago, Koyomi; Isobe, Junko; Kanatani, Junichi; Kawagishi, Yukio; Sakamaki, Ippei; Yamamoto, Yoshihiro (Internal Medicine, 2018)
Mycobacterium bovis infection after intravesical Bacillus Calmette-Guérin (BCG) therapy is rare. A 65-year-old Japanese man with history of bladder cancer and intravesical BCG therapy, presented with low-grade fever. An aneurysm with perianeurysmal fluid was suspected and endovascular aortic repair was performed. After 160 days, he developed blood-streaked sputum and computed tomography images revealed that the perianeurysmal fluid area was increasing in size. A multiplex polymerase chain reaction using sputum identified M. bovis. Treatment with anti-tuberculosis drugs reduced the size of the perianeurysmal fluid area. After intravesical BCG therapy, the possibility of M. bovis infection should be considered, thus further investigations are required.